Analysis of Rubber Marketing Efficiency in Anggokoti Village Buke District South Konawe - Muninggar, Dewi Maulana; Iswandi, R Marsuki; Surni, Surni (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This study aims to analyze the efficiency of rubber marketing in Anggokoti Village, Buke District, South Konawe Regency. The research was conducted from December 2019 to January 2020. This research was carried out in Anggokoti Village, Buke District, South Konawe Regency, from December 2019 to January 2020. The population in this study was one rubber trader in Anggokoti Village with 102 rubber farmers. The sampling technique was simple random sampling which was used to select 50 rubber farmers. Analysis of the data used is a qualitative analysis presented in the form of descriptive analysis. The results showed that rubber marketing in Anggokoti Village had a marketing margin of Rp. 1,800/Kg, and the percentage of the share price received by rubber farmers (farmer share) was 76.92%, which indicates that rubber marketing in Anggokoti Village has been running efficiently.